Vigilant existence in the earthly life. Yet again about the predominant feature in Bolesław Leśmian's poetry = Czujne istnienie w doczesności. Raz jeszcze o dominancie w poezji Bolesława Leśmiana - Łukaszuk, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The given article concerns a significant problem in the reflection about the works of B. Leśmian. On his poetic ontology, i.a. M. Głowiński, J. Trznadel, Z. Łapiński, have written. The authoress arranges research perspectives. By suggesting careful reading of the works, she considers that the dominant character of the Leśmian's poetic imagination is positive "ontology": the strong being and the reality of the world.
Keywords: Leśmian, Bolesław (1877-1937); Poezja polska - 19-20 w.; ontologia; wyobraźnia poetycka; Świat; istnienie; afirmacja; poetry; ontology; poetic imagination; world; existence; affirmation